Bridging Education and Psychology: An Interdisciplinary View on Developing Self-regulated Learning - Hačatrjana, Liena; Namsone, Dace; Martinsone, Baiba; Čakāne, Ildze (Journal of Education Culture and Society, 2026)
Thesis. Self-regulated learning is defined in policy documents as one of the core transversal skills students must develop, and psychology theories offer clear theoretical definitions about constructs related to these skills. However, research indicates that implementation of classroom-level activities aimed at developing self-regulated learning is not clear for all teachers, leading to vast differences in practice. Therefore, the aim of this paper is to offer an interdisciplinary mapping of concepts that are related to self-regulated learning and lead to development of self-regulated learning – executive functions and self-regulation, based on research in psychology and education; and to offer an output – practical guide of specific teachers’ actions for developing students’ self-regulated learning in the classroom. Concept. This study is designed as a conceptual theory-synthesis article with an embedded secondary analysis of classroom observation data used to contextualise the problem of implementing self-regulated learning in Latvia. Conceptual mapping of three important constructs – cognitive executive functions, self-regulation and self-regulated learning – is presented. A practical material for developing self-regulated learning at the classroom level is offered, including specific activities that teachers can implement in every lesson. Results and conclusions. Based on the authors’ conceptual model that represents how three constructs (executive functions, self-regulation and self-regulated learning) interact, we conclude that effective implementation of SRL development should be interdisciplinary by involving professionals from psychology and education fields. The support for teachers should be grounded in theory, as well as offer clear practical steps of actions for teachers, such as the output material of the current research.